First report of Echthrogaleus denticulatus (Smith 1874) on the pelagic thresher shark (Alopias pelagicus Nakamura 1935) from Indian EEZ of Andaman Sea - Pradeep, H.D.; Arun Kumar, M.; Swapnil, S.S (Penerbit Universiti Kebangsaan Malaysia, 2017)
The present study reports the occurrence of the pandarid parasite, Echthrogaleus denticulatus as an ectoparasite on the pelagic thresher shark (Alopias pelagicus) from the Indian EEZ of Andaman Sea. A total of 36 parasite specimens were found aggregated near the cloacal aperture of eight pelagic thresher sharks caught as bycatch by multifilament tuna longliner MFV Blue Marlin during July 2015 and February 2016 voyages in Andaman and Nicobar waters. This is the first report of ectoparasite from the Indian EEZ of the Andaman Sea.